The Role of Tat Twam Asi Teachings in Leader Member - Exchange Mediated by Teamwork towards BUMDes Employee Performance In Buleleng Regency - Ketut Sudarnaya (Department of Guidance and Counseling, FIP, Undiksha, 2021)
The Law Number 6 of 2014 concerning Villages, gives enthusiasm for villages to initiate themselves by creating the spirit of “Building Village” then BUMDes is born as an independent business institution for rural communities and will be able to develop its potential, if BUMDes pays close attention to the performance of employees is one of the factors that play an important role in achieving organizational goals. The purpose of this study is to explain the effect of leader member-exchange (LMX) and teamwork as a mediating variable on employee performance, both direct and indirect effects. The results showed that leader member-exchange (LMX) has a positive and significant effect on employee performance, teamwork has a positive and significant effect on employee performance and teamwork is a partial mediator of the influence of leader member-exchange (LMX) on the performance of BUMDes employees in Buleleng Regency. This research can provide knowledge and understanding for stakeholders in implicating teamwork in the relationship between leaders and subordinates (LMX) in improving employee performance.